(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
ABSTRACT: Interest rates are one of the important aspects that affect the banking business directly, which is characterized by unstable dynamic dynamics, which must be viewed on a daily and continuous basis through the macroeconomic view, which directly affects the bank’s income realized from loans as interest received or interest paid on its deposits as an expense. Hence the earnings per share. The relationship between interest rates and between net income and earnings per share was measured and a correlation was found between them, and then the effect between them was measured using regression equations and they were applied and the results were extracted by using the (SPSS- v.20) program and extracting the relationship and the effect supports each other. The results showed that there is a very weak correlation between interest rates and net interest income, which was explained by the fact that the loans granted are priced at a fixed interest rate and are not affected by the change in interest rates, but new loans are affected. As for the earnings per share, it showed a negative inverse relationship of 52.2%. Almost half.